CCR2 improves tumor directed CAR-T cell trafficking in ovarian cancer - Kumar, Raj; Veillard, Irva E.; Xu, Mengyao; Al-Alem, Linah; Rueda, Bo R.; Yeku, Oladapo O. (Frontiers in Pharmacology, 2025)
Solid tumors present a significant challenge to Chimeric Antigen Receptor (CAR) -T cell therapy, primarily due to limited T-cell infiltration and persistence in the tumor microenvironment. Cancers with predominantly peritoneal metastasis like ovarian cancer pose a substantial trafficking challenge to systemically administered CAR-T cell therapy. To identify chemokines that may guide CAR-T cells to tumor sites, we evaluated chemokine expression in primary and metastatic tumor samples from patients with ovarian cancer by immunohistochemistry. After identifying CCL2 as the most common chemokine expressed in both primary and metastatic disease, we validated CCL2 levels in serum samples from these patients. We found that CCL2 and CCL4 were commonly expressed in several ovarian cancer cell lines, a patient-derived tumor cell line and patient serum samples in vitro. We engineered armed Muc16/CA-125-directed CAR-T cells with cognate receptors for CCL2 and CCL4 and showed significant in vitro and in vivo tumor-directed trafficking. Finally, intravenously administered CCL2-armored CAR-T cells significantly prolonged survival in peritoneal tumor bearing mice. In conclusion, we identified CCL2 as a commonly expressed chemokine in patients with local and metastatic ovarian cancer and successfully demonstrate that armed CAR-T cells with enhanced homing to CCL2-expressing ovarian cancer are more efficacious due to improved peritoneal trafficking in vivo.